化简并求值3a+abc-1/3c^2-3a+1/3c^2,其中a=-1/6,b=2,
3个回答
3a+abc-1/3c^2-3a+1/3c^2
=(3a-3a)+abc+(1/3c^2-1/3c^2)
=abc
=1
相关问题
先化简再求值:-1/2a^2b-[3\2a^2b-3(abc-1\3a^2c)-4a^2c]-3abc,其中a=-1,b
化简并求值:1/2*a-[4b-c-(1/2*a-c)]+[6a-(b-c)],其中a=0.1,b=0.2,c=0.3
化简:x+(5x-3y)-(x-2y),化简与求值:1/3a-【1/2a-4b-6c]+3(2b-2c),其中a=6,b
1.先化简,在求值.3a+abc-1/3c²-3c²-3a+1/3C²,其中a=-1/6,
先化简,再求值:−12a2b−[32a2b−3(abc−13a2c)−4a2c]−3abc,其中a=-1,b=-3,c=
化简并求值:(3a+1)^2-2(3a+1)+3,其中a=√2
先化简再求值:3a^2b-[2a^2b-(2abc-a^2b)-4a^2c]-abc,其中a=-2,b=-3,c=1
先化简,再求值3a-(abc)+(-1/3c2)-3(a-1/9c2),期中a=-3 b=-1/6,c=2已知15x2y
先化简,再求值:5abc-2a2b-[3abc-(4a2b-a2b)],其中a=2,b=3,c=-1.
先化简,再求值:5abc-2a2b-[3abc+2(2ab2-a2b)],其中a=−12,b=-1,c=3.